Analisis Gugus Fungsi Terhadap Perbandingan Metode Pencampuran dan Metode Pengolesan Bakteri E.Coli Pada Aspal - Stefi Monika; Ratnawulan (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigated the functional group transformation of asphalt modified using Escherichia coli through mixing and coating methods as a biological self-healing approach for pavement materials. The experimental research was conducted under controlled laboratory conditions using Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscope (SEM), and hydrophobicity analysis to evaluate chemical, morphological, and surface performance changes. The mixing method promoted dominant internal interactions within the asphalt matrix, indicated by increased O–H functional groups and homogeneous bacterial distribution. In contrast, the coating method generated stronger surface reactions characterized by higher C–O intensity, enhanced biomineralization activity, and localized CaCO3 formation on the asphalt surface. SEM observations revealed that the coating method formed denser biofilm structures, contributing to improved hydrophobicity and accelerated microcrack healing performance. Comparative analysis demonstrated that bacterial application mechanisms significantly influenced asphalt chemical evolution and engineering behavior. The findings indicate that biologically modified asphalt using Escherichia coli possesses considerable potential for sustainable, adaptive, and self-healing pavement systems through optimized bacterial treatment strategies.